LESSONS FROM THE RUSSIA 2018 SOCCER WORLD CUP (Fiep Bulletin - online, 2020)
This paper about the 2018 Russian Football World Cup aims to analyze the technical aspects of matches that contribute to promote situations without objectivity and reduce the time of the ball in play and propose suggestions for, based on the data obtained in the World Cup 2018, reduce the deficiencies of these aspects in Brazilian soccer. The situations that contribute to the decrease of the playing time were considered: the kicks without direction, the concession of the lateral throw, the crossings and the fouls. Made use of the comparative method to analyze world soccer considering the results obtained in the Russian Cup. The matches were watched and match data collected from June and July 2018 with representations of the ranked teams of the five continents. Then the data analysis was performed; the comparison of players' actions during matches; and changes were proposed in order to improve the performance (results) of the Espírito Santo and Brazilian teams. Through the results of the research we suggest measures that provide changes in the state of Espírito Santo and Brazilian soccer towards a better future.